2001
DOI: 10.1210/jcem.86.12.8085
|View full text |Cite
|
Sign up to set email alerts
|

PRL as a Novel Potent Cofactor for Platelet Aggregation

Abstract: Pregnancy (including puerperium) is a period of hypercoagulability and seems to be an independent major risk factor for venous thromboembolism (VTE). However, the basis of the increased risk of VTE in pregnancy and around delivery is unknown. We hypothesized that changes in PRL, which is a prominently increased hormone during pregnancy and lactation, might be involved in the activation of platelets. To investigate platelet functional abnormalities in pregnancy, we assessed the ADP-stimulated and nonstimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
64
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 30 publications
11
64
5
Order By: Relevance
“…CD62p was not correlated to PRL values ( r 2 = −0·012; P > 0·05). This finding is in contrast to our results in other patient‐groups [4] but can be explained by the low PRL values in our patients with CHF. Previously we have demonstrated in vitro that PRL enhances ADP‐stimulated CD62p expression in a dose‐dependent manner starting at PRL values greater than 10 ng mL −1 [4].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…CD62p was not correlated to PRL values ( r 2 = −0·012; P > 0·05). This finding is in contrast to our results in other patient‐groups [4] but can be explained by the low PRL values in our patients with CHF. Previously we have demonstrated in vitro that PRL enhances ADP‐stimulated CD62p expression in a dose‐dependent manner starting at PRL values greater than 10 ng mL −1 [4].…”
contrasting
confidence: 99%
“…In our series of 50 patients with CHF (66·9 ± 12·6 years; EF: 22 ± 9%), we demonstrated significantly reduced serum levels of IL‐10, an anti‐inflammatory cytokine, revealing the inflammatory milieu in CHF [5]. To further elucidate the influence of hyperprolactinaemia in CHF on platelet activation, we retrospectively studied PRL values in the sera of our patients and compared these results with CD62p expression on platelets as previously described [4,6].…”
mentioning
confidence: 99%
“…Similarly, drug induced atrial fibrillation would be an unlikely explanation for such a rapid increase in the risk of cerebrovascular adverse events. Potential mechanisms for cerebrovascular events related to atypical antipsychotics might include orthostatic hypotension in patients with pre-existing cerebrovascular disease, which might lead to “watershed” strokes,14 and antipsychotic induced hyperprolactinaemia, which might promote platelet aggregation 14 30. Others, however, have reported that risperidone may inhibit platelet aggregation (through serotonin receptor antagonism), rather than promote it 31.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, over-sedation induced by antipsychotic use may result in dehydration and hemoconcentration, which may be potential mechanisms for increased stroke risk [22]. The association of antipsychotics with stroke may be partially explained by their hyperprolactinemia effect, which may promote platelet aggregation [23], [24]. However, several studies have reported that antipsychotics may inhibit platelet aggregation through serotonin receptor antagonism rather than promote it [25].…”
Section: Discussionmentioning
confidence: 99%